Keterlibatan Masyarakat Dalam Kegiatan Pariwisata Di Kecamatan Simanindo Kabupaten Samosir - Syahrul, Syahrul; Hasriyani, Enny; Hutahaean, Theresia (Journal of Tourism and Creativity, 2022)
This is a descriptive qualitative research that describes the involvement and the interest of local people in tourism development in the research areas. This research takes some people as repondents, they are local governments, community leaders, youth leaders and the people in the areas of research. The research shows that the supports of the local people towards the tourism in the areas are very good. They concern to the cleanliness of the environment by doing â€œgotong royongâ€ and also they keep the environment securities. The tourism sector also can increase the economic social of the local people, where they get job and also they have opportunities to do business. The other effects of tourism development also can growthe interests of the people especially for the teenagers, where they now improve their skills in traditional dancings. They also have more awareness in preserve the ulos weave, and historical building.